The Effectiveness of Plyometric Training on Agility and Speed of U-15 Badminton Athletes - Nugroho, Nabil Taufiqurrahman; Suratman, Suratman (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effectiveness of plyometric training on agility and speed in U-15 badminton athletes in Purbalingga Regency. The research employed a non-experimental quantitative approach using a survey design involving 15 athletes from PB Bina Tangkis who regularly participated in programmed plyometric training. Data were collected using the Illinois Agility Run to assess agility and the 30-meter Sprint Test to assess speed. Normality testing indicated that the data were normally distributed; however, homogeneity testing revealed non-homogeneous data, necessitating the use of the Mann-Whitney test. The analysis results showed a significance value of 0.000 (<0.05), indicating a significant difference between agility and speed test results. The mean rank speed was higher than the agility, suggesting that plyometric training had a greater effect on improving speed. These findings support the evidence that plyometric training is effective in enhancing athletes’ physical attributes, particularly speed and agility. However, since this study is non-experimental, further research with an experimental design is recommended to obtain stronger causal evidence